Development Data Analysis (DEA) Model to Evaluate the Efficiency of Professional Industrial Engineering Schools in Peru with a Sustainable Development Approach - T. Huamaní, Gloria (2016)
This paper proposes a methodology to formulate a Model of Data Envelopment Analysis (DEA) to evaluate the efficiency of Industrial Engineering careers in Peru with a sustainable development approach.This study comprises two stages, the first one corresponds to the identification of input and output variables, based on other DEA studies applied in higher education, revision of criteria used in university ranking´s, SUNEDU and ABET. In a second stage, three models are proposed whose application is restricted to the availability of data and information.